REPRESENTASI FLORA DAN FAUNA DALAM NOVEL UPACARA KARYA KORRIE LAYUN RAMPAN (REPRESENTATION OF FLORA AND FAUNA IN THE NOVEL â€œUPACARAâ€ BY KORRIE LAYUN RAMPAN) - Retno Sari Maulida (Universitas Lambung Mangkurat, 2023)
Â AbstractRepresentation of Flora and Fauna in The Novel â€œUpacaraâ€ By Korrie Layun Rampan. This study describes the flora and fauna, as well as their relationship with the novel's intrinsic elements. This type of research is literary ecology with a qualitative descriptive method. The data in this study are written data relating to flora and fauna. The data source, namely the library data source, is in the form of a novel â€œUpacaraâ€ by Korrie Layun Rampan. The data was collected using documentation studies and data analysis techniques, namely content analysis. Based on the data analysis, it was found that many flora and fauna contained in the novel are closely related to basic needs, livelihoods, traditional ceremonies, to the beliefs of the Benuaq Dayak people as told in the novel. Flora and fauna serve as a minor theme in the novel. Fauna diction is used to describe the characters in this novel, namely the proboscis monkey and hornbill. The depiction of the characters of these figures uses analytic techniques and dramatic techniques. Flora and fauna are also described as having a relationship with the setting (place, time, and social) in the novel. The relationship between flora and fauna with the point of view used by the author is not found in this novel. Flora and fauna are also described in relation to the implied mandate in this novel, namely to preserve nature, not to be greedy, and to be responsible for all actions. Keywords: Representation, Flora, Fauna, Literary EcologyAbstrakRepresentasi Flora dan Fauna dalam Novel Upacara Karya Korrie Layun Rampan. Penelitian ini mendeskripsikan flora dan fauna, juga hubungannya dengan unsur intrinsik novel tersebut. Jenis penelitian ini yaitu ekologi sastra dengan metode deskriptif kualitatif. Data pada penelitian ini adalah data tertulis yang berkenaan dengan flora dan fauna. Sumber datanya, yaitu sumber data pustaka, berupa Novel Upacara karya Korrie Layun Rampan. Data tersebut dikumpulkan menggunakan studi dokumentasi dan teknik analisis datanya, yaitu analisis isi. Berdasarkan analisis data, ditemukan banyak flora dan fauna yang termuat dalam novel yang berkaitan erat dengan kebutuhan pokok, mata pencaharian, upacara adat, hingga kepercayaan masyarakat Dayak Benuaq yang diceritakan dalam novel. Flora dan fauna dijadikan sebagai tema minor dalam novel tersebut. Diksi fauna digunakan sebagai penyebutan tokoh dalam novel ini, yaitu bekantan dan burung rangkong. Penggambaran karakter tokoh-tokoh tersebut menggunakan teknik analitik dan teknik dramatik. Flora dan fauna juga digambarkan mempunyai hubungan dengan latar (tempat, waktu, dan sosial) dalam novel. Hubungan flora dan fauna dengan sudut pandang yang digunakan pengarang, tidak ditemukan dalam novel ini. Flora dan fauna juga digambarkan berhubungan dengan amanat tersirat dalam novel ini, yaitu jagalah kelestarian alam, jangan serakah, dan bertanggung jawab atas segala perbuatan.Kata-kata kunci: Representasi, Flora, Fauna, Ekologi Sastra